Tuning crystal structure and redox potential of NASICON-type cathodes for sodium-ion batteries - Ma, Xuemei; Cao, Xinxin; Zhou, Yifan; Guo, Shan; Shi, Xiaodong; Fang, Guozhao; Pan, Anqiang; Lu, Bingan; Zhou, Jiang; Liang, Shuquan (Nano research, 2020)
Sodium superionic conductor (NASICON)-type compounds have been regarded as promising cathodes for sodium-ion batteries (SIBs) due to their favorable ionic conductivity and robust structural stability. However, their high cost and relatively low energy density restrict their further practical application, which can be tailored by widening the operating voltages with earth-abundant elements such as Mn. Here, we propose a rational strategy of infusing Mn element in NASICON frameworks with sufficiently mobile sodium ions that enhances the redox voltage and ionic migration activity. The optimized structure of Na 3.5 Mn 0.5 V 1.5 (PO 4 ) 3 /C is achieved and investigated systematically to be a durable cathode (76.6% capacity retention over 5,000 cycles at 20 C) for SIBs, which exhibits high reversible capacity (113.1 mAh·g −1 at 0.5 C) with relatively low volume change (7.6%). Importantly, its high-areal-loading and temperature-resistant sodium ion storage properties are evaluated, and the full-cell configuration is demonstrated. This work indicates that this Na 3.5 Mn 0.5 V 1.5 (PO 4 ) 3 /C composite could be a promising cathode candidate for SIBs.